Pengaruh Lingkungan Kerja terhadap Kinerja Tenaga Pendidik di SMK Negeri 14 Samarinda - Setyoningrum, Muthia Umi; Noor, Maidi; Suratman, Suratman (Borneo Journal of Islamic Education, 2023)
Abstract Among the many things that can influence the performance of teaching staff, one of them is the work environment. The performance of teaching staff can be influenced by the quality of their working conditions, so that improving the quality of the workplace will have a positive impact on teacher performance. Based on initial observations, the conditions of the teacher's working environment at SMK Negeri 14 Samarinda, namely the teacher's room, are good. Some teachers stated that they were comfortable working in the teacher's room, but some preferred working outside the teacher's room. This encouraged researchers to investigate the influence of the work environment on the performance of teaching staff at SMK Negeri 14 Samarinda. This research is quantitative descriptive. This research was conducted at SMK Negeri 14 Samarinda. Using a saturated sampling technique from a population of 46 teaching staff. Data collection methods include questionnaires and documentation. The data analysis techniques used include prerequisite testing and hypothesis testing. The results obtained from this research show that the work environment influences the performance of teaching staff by 9.78% while the remaining 90.22% is influenced by other factors. The research produced an rxy value of 0.312 based on this data. If referring to the interpretation table, a correlation with an r value between 0.20 to 0.40 can be considered a weak correlation and has a positive nature. This means that there is a relatively weak relationship between two variables and the direction of the relationship is positive, meaning that when the value of one variable increases, the value of the other variable tends to also increase, even though the relationship is not as strong. From the results of the t test, it is known that the tcount value is 2.295 and the ttable value is 1.681. With these results, we reject Ho and accept Ha, and draw the conclusion that there is a positive and significant influence between the work environment on the performance of teaching staff at SMK Negeri 14 Samarinda. Keywords: Work Environment, Performance, Educator Abstrak Di antara banyak hal yang dapat mempengaruhi kinerja tenaga pendidik salah satunya ialah lingkungan kerja. Kinerja tenaga pendidik dapat dipengaruhi oleh kualitas kondisi kerjanya, sehingga peningkatan kualitas tempat kerja akan berdampak positif terhadap kinerja guru. Berdasarkan pengamatan awal, kondisi lingkungan kerja guru di SMK Negeri 14 Samarinda yakni ruang guru baik. Beberapa guru menyatakan nyaman bekerja di ruang guru namun beberapa lebih senang bekerja di luar ruang guru. Hal ini mendorong peneliti untuk menyelidiki pengaruh lingkungan kerja terhadap kinerja tenaga pendidik di SMK Negeri 14 Samarinda. Penelitian ini merupakan deskriptif kuantitatif. Penelitian ini dilakukan di SMK Negeri 14 Samarinda. Menggunakan teknik sampling jenuh dari 46 populasi tenaga pendidik. Metode pengumpulan data meliputi angket dan dokumentasi. Teknik analisis data yang digunakan meliputi uji prasyarat dan uji hipotesis. Hasil yang diperoleh dari penelitian ini terdapat pengaruh lingkungan kerja terhadap kinerja tenaga pendidik sebesar 9,78% sementara sisanya 90,22% dipengaruhi oleh faktor lain. Penelitian menghasilkan nilai rxy sebesar 0,312. Jika mengacu pada tabel interpretasi, korelasi dengan nilai r antara 0,20 hingga 0,40 dapat dianggap sebagai korelasi yang lemah dan memiliki sifat positif. Hal ini berarti bahwa terdapat hubungan yang relatif lemah antara dua variabel dan arah hubungannya adalah positif, yang berarti bahwa saat nilai satu variabel meningkat, nilai variabel lainnya cenderung juga meningkat, meskipun hubungan tersebut tidak begitu kuat. Dari hasil uji t, diketahui nilau thitung sebesar 2,295 dan nilai ttabel sebesar 1,681. Dengan hasil ini maka menolak Ho dan menerima Ha, dan menarik kesimpulan bahwa terdapat pengaruh positif dan signifikan antara lingkungan kerja terhadap kinerja tenaga pendidik di SMK Negeri 14 Samarinda. Kata kunci: Lingkungan Kerja, Kinerja, Tenaga Pendidik